Modeling, Altitude Control, and Trajectory Planning of a Weather Balloon Subject to Wind Disturbances - Cândido, Bruno; Rodrigues, Catarina; Moutinho, Alexandra; Azinheira, José Raul (Aerospace, 2025)
Weather balloons are a popular tool to obtain atmospheric data. One of the biggest advantages of using this type of vehicle for scientific research is their inexpensiveness, as they are only composed of an inflated envelope, a parachute, and a sonde. However, their flight is dependent on the atmospheric conditions, and their life cycle is short. Thus, altitude control for weather balloons, along with trajectory planning, is a major area of interest, as it would allow one to mitigate the disadvantages while maintaining the benefits. This article presents a novel, efficient, lightweight, and cost-effective framework for weather balloon control and path planning. The proposed solution integrates a P-D cascade controller for altitude control, adapted specifically to the dynamics and actuation constraints of weather balloons, with a wind-based trajectory planner built on the A* algorithm. To the best of the authors’ knowledge, this planner is the first to incorporate wind constraints in a grid-based search tailored for weather balloon navigation. By commanding the ballast release for ascent and helium venting for descent, the developed control solution proves efficient and robust in simulation, guiding the balloon to reach defined goals while traveling through predetermined waypoints. However, it demonstrates limitations in maintaining the balloon over a fixed area.